Exploring consumer behavior in Extended Reality (XR): Analyzing key influencing factors in the metaverse - K Karthikeyan; D Prashanth (Journal of Management and Science, 2025)
This study explores the key factors shaping consumer behavior in an Extended Reality (XR) environment, focusing on customer loyalty, purchase decisions, brand perception, price sensitivity, impulse buying, channel preference, personalization, service quality, immersion level, and interactivity. While XR adoption is expanding across industries, a research gap remains in understanding the combined impact of these factors on consumer engagement and decision-making. To bridge this gap, the study employs simple percentage analysis, factor analysis, and correlation study to analyze consumer preferences and behavioral patterns. Conducted as a descriptive study in Bangalore with a sample size of 195 respondents, the research identifies interactivity and service quality as critical drivers of customer engagement, while price sensitivity and brand perception significantly influence purchase decisions. Correlation analysis further reveals strong links between impulse buying, channel preference, and purchase decisions, underscoring the role of personalized and immersive experiences in enhancing consumer satisfaction. However, low awareness levels indicate a need for targeted marketing and education to drive XR adoption. The study concludes that businesses leveraging XR should prioritize interactivity, optimize pricing strategies, and build brand trust to enhance customer engagement and loyalty.